The problem with implementing fish farms in agricultural regions: A trial in a pampean pond highlights potential risks to both human and fish health - Brodeur, Celine Marie; Poletta, Gisela Laura; Simoniello, María Fernanda; Carriquiriborde, Pedro; Cristos, Diego Sebastian; Pautasso, Nestor Abel; Paravani, Enrique Valentín; Poliserpi, Maria Belen; D'Andrea, María Florencia; González, Patricia Verónica; López Aca, Viviana; Curto, Alejandro Ernesto (Elsevier, 2020)
The safety of creating fish farms in agricultural settings was evaluated by growing Piaractus mesopotamicus in a pond, while crops where cultivated in a nearby field under a pesticide application regime typical of the Pampa region. Atrazine, glyphosate and its metabolite, aminomethylphosphonic acid (AMPA), were detected in the water of the pond at concentrations ranging between 92 and 118 μg/L for atrazine, 12 and 221 μg/L for glyphosate and 21 and 117 μg/L for AMPA. Atrazine and malathion were detected in fish muscles at concentrations ranging between 70 and 105 μg/kg for atrazine and 8.6 and 23.7 μg/kg for malathion. Compared to fish raised in a pisciculture, fish from the agricultural pond presented reduced values of pack cell volume, hemoglobin, mean corpuscular hemoglobin and mean corpuscular hemoglobin concentration, together with significantly greater cholinesterase activity in both plasma and liver and reduced glutathione-S-transferase activity in the liver. A comet assay also demonstrated that P. mesopotamicus from the agricultural pond presented a significantly greater level of DNA damage in both erythrocytes and gill cells. Overall, the present study demonstrates that pisciculture ponds established in an agricultural setting may receive pesticides applied to nearby cultures and that these pesticides may be taken up by the fish and affect their physiology and health. The accumulation of pesticides residues in fish flesh may also present a risk to human consumers and should be closely controlled.